2003
DOI: 10.1038/sj.bjc.6601239
|View full text |Cite
|
Sign up to set email alerts
|

Food groups and risk of squamous cell carcinoma of the oesophagus: a case–control study in Uruguay

Abstract: a case -control study on squamous cell cancer of the oesophagus was conducted in Montevideo, Uruguay. The main objective of the study was to estimate the odds ratios (ORs) associated with main food groups. For this purpose, 166 patients afflicted with squamous cell oesophageal cancer and 664 hospitalised controls were frequency matched on age and sex. Both series of patients were administered with a structured questionnaire. Aside from queries related with tobacco smoking, alcohol drinking and maté drinking, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 22 publications
(31 reference statements)
5
56
0
5
Order By: Relevance
“…De Stefani E reported that consuming salted meat, another kind of processed foods, was associated with higher risk of squamous cell carcinoma of esophagus, no matter in one-site or multi-site case control studies (De Stefani et al, 1999;De Stefani et al, 2003;De Stefani et al, 2009). In Netherland, one cohort study also presented the similar association between processed meat and ESCC, with the HR being 3.47 (Keszei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…De Stefani E reported that consuming salted meat, another kind of processed foods, was associated with higher risk of squamous cell carcinoma of esophagus, no matter in one-site or multi-site case control studies (De Stefani et al, 1999;De Stefani et al, 2003;De Stefani et al, 2009). In Netherland, one cohort study also presented the similar association between processed meat and ESCC, with the HR being 3.47 (Keszei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, vegetables were included in their final model, whereas fruits were not. Other reports displayed lower risks for fruits compared to vegetables 6,7,9,10,[15][16][17][18][19]23,25,33,41,43,45 (15/38, 39.5%). Thus, the following question arises: is the overall body of evidence now sufficient to Adjusted for age, sex, residence, urban/rural status, birthplace, education, smoking status, years since quit, number of cigarettes smoked per day, alcohol drinking, matè temperature, stewed meat and total energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…5 Five Uruguayan studies conducted by our group have examined the associations between foods and nutrients and oesophageal cancer risk. [6][7][8][9][10] According to these studies salted meat is a risk factor, whereas high intake of fresh fruits and vegetables was associated with strong reductions in risk. Studies conducted in other populations also reported a strong protective effect of plant foods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…V á r i o s e s t u d o s e n c o n t r a r a m u m a associação entre a temperatura da infusão da erva mate e os riscos de câncer oral, esôfago e/ou laringe (Barros et al, 2000;De Stefani et al, 2002). Assim, a causa do chá mate provocar câncer seria devida à lesão térmica pelo contato direto da mucosa com a bebida quente.…”
Section: Discussionunclassified